A Perspective on the Role of Emotions for Transformative Capacities and Climate Resilience - Friedrich, Jonathan; Grewer, Janes; Dzalbe, Sania; Engler, John-Oliver; Zscheischler, Jana (DIE ERDE – Journal of the Geographical Society of Berlin, 2026)
Emotions are a neglected topic in the study of social climate resilience and transformative capacities. Yet emotions are a key driver of human behavior. Therefore, in this article, we present a perspective on how transformative capacities are conditioned through emotions. We map different emotions and their influence and relationship to transformative processes. We find that emotions are particularly relevant in the context of problem recognition, shared responsibility, reorientation, and collective action. We conclude that emotions are central to understanding responses to and capacities for transformation and resilience building, but remain under-researched